PENGEMBANGAN KARAKTER MANDIRI MELALUI KEGIATAN ENTREPRENEURSHIP BERINTEGRITAS PADA FAKULTAS AGAMA ISLAM DI UNIVERSITAS SERAMBI MEKKAH BANDA ACEH - Hayati Hayati; Ismawirna Ismawirna; Taat Kurnita Yeniningsih (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2020)
University is a representative facility to develop independent character through entrepreneurship event at the Faculty of Islamic Studies, Universitas Serambi Mekkah, Banda Aceh. It is argued that the university can reshape the future leaders of a country. This study aims to develop an independent character through an entrepreneurship event at the Faculty of Islamic Studies, Universitas Serambi Mekkah, Banda Aceh. The long-term aim of this research is to create university alumni having high integrity, independent soul, and entrepreneurial spirit. The research designed as Research and Development (R&D) conducted within two phases. In the first phase, a survey on method and approach utilized as an input for the development of entrepreneurship learning methods. In the second phase, the trial of the entrepreneurship learning method will be conducted in the field with the involvement of students and lecturers. The research method is using a mixed method approach. As the data collection method, the researcher conducts interviews, documentation, and observation. Additionally, the Likert scale is used during quantitative research. The total population of this research is 130 students from four different departments within the Faculty of Islamic Studies. The sample itself is thirteen students from the population. The sampling technique uses purposive sampling. The data analysis technique utilizes quantitative and qualitative descriptive analysis. The results show that from 13 respondents of the entrepreneurship event, there are only two brave students who open independent businesses and new employments after finishing their studies. Both of the students are coming from the PAI department: T. Basyira opens a cafe named